2015
DOI: 10.1117/12.2078803
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency droop in nitride LEDs revisited: impact of excitonic recombination processes

Abstract: The efficiency droop in nitride LEDs is currently attributed to either carrier-density-dependent nonradiative recombination or to carrier leakage, both being discussed in terms of a single-particle picture. Our time-resolved photoluminescence results show that the radiative lifetime is independent of carrier density, while the nonradiative lifetime scales with the inverse of the carrier density. This can not be understood in a single-particle model. By means of a many-particle theory approach we obtain a consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Effective decay time, radiative lifetime, and non-radiative lifetime of a highly efficient (>80% at 300 K) GaInN/GaN MQW versus temperature. As the effective lifetime exhibits an identical temperature dependence as the radiative lifetime, the absolute value of the radiative lifetime at low temperature is identical to the measured effective lifetime [69].…”
Section: Non-and Semipolar Quantum Wellssupporting
confidence: 64%
See 1 more Smart Citation
“…Effective decay time, radiative lifetime, and non-radiative lifetime of a highly efficient (>80% at 300 K) GaInN/GaN MQW versus temperature. As the effective lifetime exhibits an identical temperature dependence as the radiative lifetime, the absolute value of the radiative lifetime at low temperature is identical to the measured effective lifetime [69].…”
Section: Non-and Semipolar Quantum Wellssupporting
confidence: 64%
“…This kind of analysis has been applied to the data of Langer et al [24] with the results shown in figure 20 [69]. The analysis shows that both radiative and Auger recombination are enhanced by approximately two and three orders of magnitude, respectively, at low carrier densities.…”
Section: Unified Picturementioning
confidence: 99%
“…Based on the existing information, 8 we are also unable to evaluate the influence of other effects such as current crowding, 10 electron leakage, 3 non-uniform Indium distribution, 39 or excitonic enhancement. 40 Further research is needed to fully understand the contribution of Auger recombination to the GaN-LED efficiency droop.…”
mentioning
confidence: 99%
“…Likewise, the B coefficient cannot be treated as a constant since, at high density, when the system gets degenerate, phase-space filling drastically reduces B [20]. Moreover, considering the large binding energy of excitons in thin InGaN/GaN QWs (both polar and nonpolar ones), exciton recombination is expected to play an important role even at room temperature [21,22].…”
Section: Introductionmentioning
confidence: 99%